Aurivela longicauda (Red-tailed Teiid). Predation - Kass, Camila Alejandra (2018)
Aurivela longicauda is an endemic lizard from the Monte Desert region of western Argentina. It is an agile lizard that is typically observed during the warm hours of the day, where it inhabits sedimentary sand or dunes with a few shrubs and scattered ground vegetation. The aim of this note is to report an observation of an A. longicauda being preyed upon by an Argentine dwarf spider, Grammostola mendozae. The predation of vertebrates by arthropods is documented worldwide. The predation event was recorded in Talampaya National Park (TNP), located in an extensive plain of the Monte region (29.8°S, 67.833°W, WGS 84; 1300 m elev.) in the center-west of La Rioja Province (Argentina), which was designated as a UNESCO World Heritage Site in 2000. At 1310 h on 11 November, during pitfall trap surveys in TNP, we found the spider feeding on the right portion of the skull, including the right eye, of an adult A. longicauda. After a few minutes, the spider dragged the lizard for a few centimeters and let it go. The lizard was collected and housed at Museo de La Plata Herpetological Collection. Our observation is the first record of predation on A. longicauda by G. mendozae.